Risk factors for severe postpartum hemorrhage in placenta accreta spectrum patients undergoing prophylactic resuscitative endovascular balloon occlusion of the aorta during cesarean delivery - Wu, Xiafei; He, Jie; Bai, Yuxiang; Gan, Yanqiong; Xu, Hongbing; Qi, Hongbo; Yu, Xinyang (Annals of medicine (Helsinki), 2025)
This study aims to investigate the risk factors for severe postpartum hemorrhage (SPPH) in patients with placenta accreta spectrum (PAS) undergoing cesarean delivery, despite the prophylactic use of resuscitative endovascular balloon occlusion of the aorta (REBOA). We conducted a retrospective case-control study on PAS patients who underwent cesarean delivery with prophylactic REBOA at the First Affiliated Hospital of Chongqing Medical University from January 2017 to December 2021. Prophylactic REBOA placement was determined by a prenatal ultrasound scoring system. Patients were divided into those who experienced SPPH (case group) and those who did not (control group), with SPPH defined by one or a combination of the following criteria: intraoperative blood loss ≥1500 mL, transfusion of ≥4 units of packed red blood cells, intraoperative hysterectomy, or sequential uterine artery embolization. Propensity score matching (PSM) was employed to minimize biases, and multivariate logistic regression was used to calculate adjusted odds ratios (aOR) for risk factors. Of the 424 enrolled patients, 102 experienced SPPH (case group), while 322 did not (control group). After PSM, the case group comprised 79 patients, and the control group included 130. After adjusting for confounders, patients with placenta increta (aOR 3, 95% CI 1.49-6.03, = 0.002), percreta (aOR 21.77, 95% CI 6.57-72.09, < 0.001), lower hemoglobin levels (aOR 0.98, 95% CI 0.95-1, = 0.050), and higher D-dimer levels (aOR 1.36, 95% CI 1.12-1.65, = 0.002) had an elevated risk of SPPH. Threshold effect analysis indicated no significant nonlinear relationship between hemoglobin, D-dimer, and outcomes. PAS patients, particularly those with placenta increta and percreta, lower hemoglobin levels, and elevated D-dimer levels, are at an increased risk of SPPH during cesarean delivery, even with REBOA intervention.